Activated carbons from Baru (Dipteryx alata Vog.) waste impregnated with copper oxide: application in the postharvest preservation of bananas - Oliveira, Ana Carolina de Jesus; Silva, Flávio Alves da; Oliveira, Tatianne Ferreira de; Valdés , Héctor (Food Science and Technology, 2025)
Banana is an agricultural commodity cultivated extensively in tropical and subtropical regions with consumption demand worldwide. During the ripening process, several biochemical reactions occur that are linked to the production of ethylene, which determines the shelf life and quality of the fruit. Ethylene can promote excessive ripening and decay of fruits and vegetables, even at very low concentrations. Therefore, an ethylene control strategy needs to be developed to address this challenge. This study aimed to evaluate the effects of using activated carbon from baru (Dipteryx alata Vog.) waste, impregnated with copper oxide, as potentially efficient materials for eliminating ethylene and maintaining postharvest quality of bananas. The developed adsorbent materials showed high ethylene adsorption capacity, validating their potential application in real storage conditions for climacteric fruits. The evaluation of quality attributes, like color, firmness, weight loss, total titratable acidity, total soluble solids, and total soluble solids/total titratable acidity ratio, confirmed the effectiveness of activated carbon and activated carbon impregnated with copper oxide in delaying the ripening and senescence process compared to bananas in the control group. The results of this study contribute to the development of ethylene adsorbent materials that combine sustainability and efficiency, with promising applications in the food industry to reduce postharvest losses.